4D visualisation of in situ nano-compression of Li-ion cathode materials to mimic early stage calendering. Issue 3 (9th January 2019) - Daemi, S. R.; Lu, X.; Sykes, D.; Behnsen, J.; Tan, C.; Palacios-Padros, A.; Cookson, J.; Petrucco, E.; Withers, P. J.; Brett, D. J. L.; Shearing, P. R.
Abstract : X-ray nano-tomography was used to study the strain evolution of an NMC electrode under uniaxial compression to mimic calendering. Abstract : Lithium-ion (Li-ion) batteries operate via electrochemical reactions between positive and negative electrodes, formed by complex porous microstructures. An improved understanding of these materials can lead to a greater insight into the link between microscopic electrode morphology and macroscopic performance. The practice of calendering electrodes after manufacturing has been widely used to increase the volumetric energy density and improve the electrical contact between electrode material particles and with the foil substrate. In this paper we present, for the first time to the authors' knowledge, a technique to image battery electrodes in situ and in 3D whilst undergoing uniaxial compression with the intent of emulating the calendering process. This technique allows the tracking of electrode strain during compression and its further application will lead to a thorough understanding of crack initiation and propagation mechanisms within electrode particles, ultimately optimising their design and performance.